D‐psicose 3‐epimerase secretory overexpression, immobilization, and d‐psicose biotransformation, separation and crystallization. Issue 2 (8th August 2017) - Li, Can; Lin, Jianqun; Guo, Qingqing; Zhang, Chengjia; Du, Kai; Lin, Huibin; Lin, Jianqiang
Abstract: BACKGROUND: D‐psicose is a rare sugar and exists in extremely small quantities in nature. It has important physiological functions and is allowed to be used as an ingredient in foods and dietary supplements. The aim of this study is to develop the biotransformation, separation and purification methods for highly efficient mass production of d‐psicose. RESULTS: First, the gene of d‐psicose 3‐epimerase (DPE) from Ruminococcus sp. was cloned and overexpressed in the food‐grade microorganism Bacillus pumilus, and the recombinant protein was soluble, bioactive, and secretory overexpressed at a high level. The substrate specificity and metal ion effects of DPE were investigated. The recombinant DPE was immobilized onto anion exchange resin matrix, and the enzymatic properties and rounds of reuses of the immobilized DPE were investigated. Then, d‐psicose was produced using the immobilized enzyme, separated by simulated moving bed chromatography (SMB), and finally purified by crystallization. The purity of the d‐psicose crystal reached 99.1%. CONCLUSION: Food grade high purity d‐psicose can be efficiently produced and purified using the methods developed in this research, which can be easily scaled up for industrial‐scale mass production. © 2017 Society of Chemical Industry